Can daytime digital imaging be used for traffic sign retroreflectivity compliance?. (November 2015) - Khalilikhah, Majid; Heaslip, Kevin; Song, Ziqi
Highlights: Data of traffic signs was collected from the field using both manual and mobile methods. ArcGIS was used to find the overlaps in the two data sets and statistical methods to analyze the data. Daytime digital imaging cannot be considered a reliable alternative for sign retroreflectivity measurements. Abstract: To ensure traffic sign visibility for the information transfer between traffic signs and drivers, transportation agencies are required to achieve and maintain traffic signs to at least minimum retroreflectivity levels. To do this, the Manual on Uniform Traffic Control Devices (MUTCD) outlined two assessment methods – visual nighttime inspection and retroreflectivity measurement – and three management methods – expected life, blanket replacement, and control signs. This study aimed to examine whether or not visual condition derived from daytime digital imaging can be used to achieve sign retroreflectivity compliance. To accomplish this goal, we used two data sets. A sample data of over 1700 signs was manually collected in the field, and the background retroreflectivity of each sign was measured using a handheld retroreflectometer. In addition, sign data of over 97, 000 traffic signs was digitally collected by driving an equipped vehicle. Sign visual condition ratings (good, fair, and poor) data was obtained from inspection of daytime digital images taken of each individual sign. By focusing on the overlaps in the two data sets including almost 1500 signs, we obtained a range of retroreflectivity measurements for each sign condition. Also, we employed the basic definition of conditional probability to assess the probability of traffic sign retroreflective pass or failure, depending on whether the sign was recorded in good, fair, or poor conditions. At its completion, the study found that though daytime digital imaging cannot be considered a reliable alternative for sign retroreflectivity measurements, nighttime digital imaging may have potential for use, and both allow transportation agencies to know which signs should be investigated manually.